116k views
19 votes
Please help me answer this question its urgent

Please help me answer this question its urgent-example-1
User Eskatos
by
4.9k points

1 Answer

4 votes

Answer:

Explanation:

1).
(2)/(3)n-(3)/(4)n+(1)/(6)n+2(2)/(9)n

=
(2)/(3)n-(3)/(4)n+(1)/(6)n+(2+(2)/(9))n

=
((2)/(3)-(3)/(4)+(1)/(6))n+(2+(2)/(9))n

=
((8)/(12)-(9)/(12)+(2)/(12))n+(2+(2)/(9))n

=
((8-9+2))/(12)n+(2+(2)/(9))n

=
(1)/(12)n+(2+(2)/(9))n

=
((1)/(12)+2+(2)/(9))n

=
((3)/(36)+(72)/(36)+(8)/(36))n

=
(83)/(36)n

=
2(11)/(36)n

2).
(2)/(5)g-(1)/(6)-g+(3)/(10)g-(4)/(5)

=
((2)/(5)-1+(3)/(10))g-((1)/(6)+(4)/(5))

=
((4)/(10)-(10)/(10)+(3)/(10))g-((5)/(30)+ (24)/(30))

=
((4-10+3)/(10))g-((5+24)/(30))

=
(-3)/(10)g-(29)/(30)

=
-(3)/(10)g-(29)/(30)

3).
i+6i-(3)/(7)i+(1)/(3)h+(1)/(2)i-h+(1)/(4)h

=
7i-(3)/(7)i+(1)/(2)i+(1)/(3)h-h+(1)/(4)h

=
(7-(3)/(7)+(1)/(2))i+((1)/(3)-1+(1)/(4))h

=
((98)/(14) -(6)/(14)+(7)/(14))i+((4)/(12)-(12)/(12)+(3)/(12))h

=
((98-6+7)/(14))i+((4-12+3)/(12))h

=
(99)/(14)i-(5)/(12)h

User Romanito
by
4.5k points